ANALISIS KOMPARASI TERHADAP KUALITAS AKUNTANSI SEBELUM DAN SESUDAH PENERAPAN STANDAR AKUNTANSI KEUANGAN INTERNASIONAL DI INDONESIA ( Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2013) - Nurhikmah Esti Prastika; Yohani Yohani; Haifa’ Kurniawati (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2014)
This study aimed to test whether or not the difference between before to after the implementation of IFRSon the financial statements of the company - manufacturing companies listed in Indonesia Stock Exchange (BEI), with consideration of the impact on the qualityof accounting. This study uses earnings management, earnings persistence, timelyloss recognition and value relevance for assessing the quality of accounting. This research is an empirical study with purposive sampling techniques in data collection. Data obtained from secondary data manufacturing company's financial statements for the years 2010 to 2013. The research analyzed using Paired - Sample T test and the Chow test. These results indicate that there is a difference between before and after the implementation of IFRS on earning s management and earnings persistence. As for the relevance and value of timely loss recognition test results showed nodifference between before to after the implementation of IFRS on manufacturing companies listed in Indonesia Stock Exchange (BEI) from 2010 to 2013